KEKUATAN HUKUM PEMBUKTIAN AKTA NOTARIS AKIBAT PENYALAHGUNAAN KEADAAN - Annisa Bella Saffanah; Wardani Rizkianti (Universitas Muhammadiyah Ponorogo, 2021)
Notaries are often placed as defendants or co-defendants in civil lawsuits against the law regarding deeds that contain elements of undue influence. This journal writing focuses on the legal consequences of the state undue influence element against the Notary's authentic deed and the Notary's responsibility in making authentic deeds that contain elements of undue influence. The research method used in writing this journal is juridical normative through a statutory approach, a case approach, and a conceptual approach. The result of this research is that the legal consequences of a Notary deed that contain elements of undue influence can be canceled, degraded into deeds under the hands, can be canceled by agreement of the parties without court process, and can be canceled by the court based on the principle of legitimate presumption. As for the notary's responsibility for deeds that contain elements of abuse of circumstances are civil and administrative.